(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Nanotechnology, the latest investigation fields that has become popular worldwide from coming days swiftly rising concern in using nanoparticles in cement concrete. Nanoparticles leads to more chemical reaction at the interface, which results in enhanced properties.Nanoparticles of ZNo with 50-60 nm is investigated. The purpose of this investigation is to prepare a Cement mortar improved mechanical properties The mortar is used in this study consists of Portland Pozzolana cement (PPC) and nano zinc oxide particles. Binding material (Cement) moderately substituted by Nano Zinc oxide (NZnO). Mortar is mixed with cement as 1:2 & 1:3 and the water – binder ratio of 0.35.The compressive strength for M-40 Grade of cement mortar is obtained at 7,14,28 days in this study. It For A1 has attained 65% of initial strength within 7 days, further the same mix of 90% of intermediate strength obtained within 14 days duration and also overall 9.24% of total strength achieved by adding 0.50% of Nano-Particles as replacement of cement.From beyond 1.50% of replacement of Nano- Particles the strength consecutively reducing due to water-cement ratio, pore filling, microstructure interaction and cement paste, etc. And28 days 1:2 mix mortar gained 17.27% of enhancement while 1:3 mix mortar gained only 7.59% strength enhancement.